Ammonia-based plasma treatment of single-walled carbon nanotube thin films for bio-immobilization. (August 2016) - Lee, Jaemin; Efremov, Alexander; Son, Ryeo Gang; Pack, Seung Pil; Lee, Hyun Woo; Kim, Kwangsoo; Kwon, Kwang-Ho
Abstract: The bio-immobilization efficiency of single-walled carbon nanotube (SWCNT) thin films treated in NH3 /Ar/N2 inductively coupled plasmas with different Ar/N2 gas mixing ratios was studied. The plasma parameters as well as the densities and fluxes of the plasma active species were controlled using both plasma diagnostics (Langmuir probes, optical emission spectroscopy) and modeling. The surface morphology of the SWCNT thin films was observed by field-emission scanning electron microscopy (FE-SEM). The structural changes on the treated surfaces were detected by Raman spectroscopy. The changes in atomic composition for plasma-treated and pristine SWCNT film surfaces were analyzed by X-ray photoelectron spectroscopy (XPS). Fluorescence analysis of the plasma-functionalized SWCNT surfaces was performed with green fluorescent proteins (GFPs). It was found that the transition from NH3 /Ar to NH3 /N2 gas system at other constant processing conditions resulted in increasing the CNT surface roughness, the degree of structural defects, the number of NH2 -functional groups connected to the CNT surface and the bio-immobilization capability. It was proposed that all these effects are connected to the chemical etching and modification of SWCNTs due to the increased flux of NHx (x < 3) species.